TRADISI MENGUNYAH SIRIH DAN MEMOTONG KERBAU PADA UPACARA ADAT / HORJA DI ANGKOLA – MANDAILING - Nenggih Susilowati (Berkala Arkeologi Sangkhakala, 2017)
The betel-chewing tradition is often being related to the migration of Austronesian-speaking people from Taiwan to the Indonesian Archipelago during the prehistoric period. The culture, which continues up to later periods, becomes the tradition of almost all the tribes in the Archipelago, including the Angkola-Mandailing in North Sumatera. The goal to be achieved in this article is to learn about the function or importance of betel and buffaloes in the traditional ceremonies in Angkola-Mandailing, as well as to understand the meaning behind it. The method used here is quantitative, along with ethnographic study and Symbolic-InteractionTheory. Betel is also used in daily activities (betel-chewing or as traditional medicine) besides being part of traditional ceremonies (horja) like horja siriaon (joyful ceremonies of the birth of children, house-warming, wedding, etc.) as well as horja siluluton (ceremonies during sad times like death). During big ceremonies (horja godang), the animals being slaughtered have to be buffaloes. Horja godang is a tradition characterized by makkobar, margondang, manortor, and buffalo slaughtering activities. In relation to the Symbolic-Interaction Theory, betel and buffalo are symbols of non-verbal communications of inviting and conducting traditional ceremonies. On the other hand, they are also symbols of verbal communication in forms of words in traditional hata, which were spoken during makkobar in a horja godang.Budaya mengunyah sirih sering dikaitkan dengan migrasi penutur bahasa Austronesia dari Taiwan ke Nusantara pada masa prasejarah. Budaya ini yang berlanjut hingga masa-masa kemudian menjadi tradisi hampir semua suku-suku di Nusantara, termasuk Mandailing-Angkola di Sumatera Utara. Tujuan yang ingin dicapai dalam tulisan ini adalah untuk mengetahui fungsi atau arti penting sirih dan kerbau pada upacara adat di Angkola-Mandailing, serta mengetahui makna yang terkandung di dalamnya. Metode yang digunakan adalah kualitatif dengan kajian etnografi serta diterapkan Teori Interaksi Simbolik. Sirih juga digunakan dalam kehidupan sehari-hari (tradisi makan sirih atau sebagai obat), dan juga penting dalam kegiatan adat (horja) seperti horja siriaon (upacara adat suka cita-kelahiran anak, memasuki rumah baru, perkawinan) maupun horja siluluton (upcara adat duka cita-kematian). Apabila yang dilaksanakan adalah upacara adat besar (horja godang) maka hewan yang disembelih wajib kerbau. Horja godang merupakan kegiatan adat yang ditandai dengan kegiatan makkobar, margondang, manortor, dan menyembelih kerbau. Di dalam kaitannya dengan Teori Interaksi Simbolik, sirih dan kerbau merupakan bentuk komunikasi non verbal sebagai simbol undangan dan penyelenggaraan kegiatan adat. Di sisi lain sebagai bentuk komunikasi verbal melalui perkataan dalam hata adat yang terucap dalam makkobar pada suatu horja godang.